Effectiveness of Reablement: A Systematic Review - Annie Tessier, Marie-Dominique Beaulieu, Carrie Anna Mcginn and Renée Latulippe (Healthcare Policy, 2016)
The ageing of the population and the increasing need for long-term care services are global issues. Some countries have adapted homecare programs by introducing an intervention called reablement, which is aimed at optimizing independence. The effectiveness of reablement, as well as its different service models, was examined. A systematic literature review was conducted using MEDLINE, CINAHL, PsycINFO and EBM Reviews to search from 2001 to 2014. Core characteristics and facilitators of reablement implementation were identified from international experiences. Ten studies comprising a total of 14,742 participants (including four randomized trials, most of excellent or good quality) showed a positive impact of reablement, especially on health-related quality of life and service utilization. The implementation of reablement was studied in three regions, and all observed a reduction in healthcare service utilization. Considering its effectiveness and positive impact observed in several countries, the implementation of reablement is a promising avenue to be pursued by policy makers.
Keywords: reablement, restorative, older people, aged, homecare services, activities of daily living